Primary Hydatid Cyst Posterior Triangle of Neck in a Child of 10 Years of Age - Hamid, Raashid; Shera, Altaf Hussain; Bhat, Nisar Ahmad; Khursheed, Sheikh; Baba, Aejaz A; Rasheed, Abdul; Akhter, Afrozah (Journal of Nepal Paediatric Society, 2013)
A case of hydatid cyst involving posterior triangle of neck in a 10 year old male child is reported. Diagnosis was confirmed by MRI. Surgical excision of the cyst was done. Hydatid cyst in posterior triangle should be considered one of the possibilities in evaluating a cystic swelling in this region. DOI: http://dx.doi.org/10.3126/jnps.v32i3.5768 J. Nepal Paediatr. SocVol.32(3) 2012 261-262